2016
DOI: 10.4238/gmr.15027816
|View full text |Cite
|
Sign up to set email alerts
|

Acrocomia aculeata prevents toxicogenetic damage caused by the antitumor agent cyclophosphamide

Abstract: ABSTRACT. Acrocomia aculeata is a plant rich in antioxidant compounds. Studies suggest that this plant has anti-inflammatory, antidiabetic, and diuretic potential. We assessed the antigenotoxic, antimutagenic, immunomodulation, and apoptotic potentials of A. aculeata alone and in combination with an antitumor agent, cyclophosphamide. Swiss male mice (N = 140) were used. The animals were divided into 14 experimental groups as follows: a negative group, a positive group (100 mg/kg cyclophosphamide), groups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
6
0
5
Order By: Relevance
“…In a systematic analysis, biometric parameters do not indicate excessive weight loss that would correlate to toxicity (Magosso et al, 2016). Also, no changes were observed in the behavior or in variations in feed intake or water.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic analysis, biometric parameters do not indicate excessive weight loss that would correlate to toxicity (Magosso et al, 2016). Also, no changes were observed in the behavior or in variations in feed intake or water.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Magosso et al. () reported that A. aculeata prevented toxicogenetic damage caused by CP in mice. However, it is necessary to do more investigation about this fruit before its incorporation as an oil source and functional food, as little pharmacological information is known about this species.…”
Section: Introductionmentioning
confidence: 98%
“…Several side effects have been associated to CPA use such as nephrotoxicity, gonadotoxicity, and possible cardiotoxic effects. In order to reduce CPA toxicity, different chemotherapy schemes and strategies have been proposed, as well as adjuvants [ 16 , 17 , 25 ]. Among these strategies, the sensitization of cancer cells to CPA antitumor effect by increasing the expression of enzymes related to its activation [ 7 , 8 , 9 , 15 ] has been addressed.…”
Section: Discussionmentioning
confidence: 99%